2012
DOI: 10.1111/j.1478-5153.2012.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse workload in implementing a tight glycaemic control protocol in a UK hospital: a pilot time‐in‐motion study

Abstract: The episodic data of our pilot study in the UK contributes further evidence that TGC protocols may be arduous to maintain and constitute a substantial investment of nursing time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
0
17
0
7
Order By: Relevance
“…Y cuando se realiza en la práctica geriátrica, predispone a mayores riesgos relacionados tanto con la práctica de multifármacos, como de aparición de efectos adversos. Estando el error de medicación caracterizado como un evento evitable, ocurrido por el uso del medicamento, que puede causar daño o no al paciente (19,(26)(27)(28)(29) . Se trata de un procedimiento rutinariamente realizado por la enfermería, exigiendo, para su práctica, de conocimiento científico y técnico que posibilite el desarrollo de prácticas seguras (12) .…”
Section: Líneas De Cuidado Y Solvencia Asistencialunclassified
See 1 more Smart Citation
“…Y cuando se realiza en la práctica geriátrica, predispone a mayores riesgos relacionados tanto con la práctica de multifármacos, como de aparición de efectos adversos. Estando el error de medicación caracterizado como un evento evitable, ocurrido por el uso del medicamento, que puede causar daño o no al paciente (19,(26)(27)(28)(29) . Se trata de un procedimiento rutinariamente realizado por la enfermería, exigiendo, para su práctica, de conocimiento científico y técnico que posibilite el desarrollo de prácticas seguras (12) .…”
Section: Líneas De Cuidado Y Solvencia Asistencialunclassified
“…Lo que justifica, para algunos autores, la realización de la estandarización y uniformidad de las prácticas en el intento de minimizar las chances de errores y la realización de técnicas por imprevisibilidad (16,(28)(29)(30)(31)(32) El fallo en la comunicación contribuye a la situación del error, siendo que su práctica, cuando realizada de forma satisfactoria, puede ayudar en la promoción y mantenimiento de un ambiente seguro. Esta comunicación es facilitada cuando se da en la realización de un trabajo en equipo, con diálogo abierto acerca del error (18,19).…”
Section: Líneas De Cuidado Y Solvencia Asistencialunclassified
“…Adaptive model-based protocols for accurate glycaemic control (AGC) that modulate insulin and nutrition have shown considerable promise in the intensive care unit (ICU) [6][7][8][9][10]. However, they are not suitable for less acute wards because of the demands they place on clinical staff [11][12][13][14] and the lack of intravenous (IV) lines for IV delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of a fully computerized algorithm for glucose control and the high familiarity of the protocol among our IC nurses may have contributed to the low incidence of severe hypoglycemia. The available studies to date on tight glucose control showed an increase in nursing workload [21][22][23]. The potential benefits of CGM in the reduction of blood samples, blood loss and nursing workload was assumed in previous studies, but was not systematically assessed before.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…This finding seems clinically relevant, especially in a busy clinical IC environment. Two studies focused on the cumulative nursing workload accompanied with tight glucose control protocols [21,22]. Gartemann et al estimated that nurses devoted approximately 42 minutes during a 12-hour shift of their time to administering a tight glycemic control (TGC) protocol, whereas Aragon et al even reported that up to 2 hours might be required for tight glycemic control for a single patient in a 24-hour period.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%